Miguel Angel De Marco, (H), Carlos Sylvestre Begnis. Liderazgo y gobierno en el desarrollo del litoral argentino, Buenos Aires, Dunken, 2005, 976 pp. - Amaral, Samuel (2005)
Fil: Amaral, Samuel. Investigador independiente; Argentina